Event “Ngawangkong” Humas Pemerintah Daerah Kabupaten Bandung - Rieska Arsheila Sutama; Leili Kurnia Gustini; Heddy Setiawan (KOMVERSAL, 2023)
The Public Relations of Bandung Regency is a regional apparatus that plays an important role in the progress of existing programs in the Bandung Regency Government. In early 2018 the Regent of Bandung H Dadang Naseer made a program that aims to establish good friendship between the Bandung regency government and the media press crew.The research contained in to find out how the efforts of the Public Relations of Bandung Regency in building a reputation, improving coordination with the media and improving facilities in this ngawangkong event. The research method used is descriptive qualitative method, namely describing, describing, and analyzing based on the results of research at the Regional Secretariat of Bandung regency. The data collection conducted by researchers includes the case study method by finding direct information based on facts in the field, then also using the method of observation, interviews and documentation. The author concludes that the non-work event for the public relations of the Bandung regency regional secretariat is going well.